Testing for HIV infection in the emergency departments of 2 hospitals in the Southeastern United States - Rachel Safeek; Tamsey Hill; Arthur Hendricks; David Underwood; Mary Washington; Jessica Guidici; Tammy Wong; Charles Gerardo; Charles Hicks; Mehri McKellar (Journal of the American College of Emergency Physicians Open)
Abstract Background In 2006, the Centers for Disease Control and Prevention (CDC) recommended non‐targeted, opt‐out HIV screening in all healthcare settings, including emergency departments (EDs). Multiple HIV testing programs have been implemented in EDs across the United States with varying designs and testing platforms. We report findings from a free, non‐targeted, rapid HIV testing program in 2 EDs in the Southeastern United States. Methods From 2008 to 2012, adults ≥18 years of age were offered free rapid HIV testing using an oral swab test (OraQuick ADVANCE Rapid HIV‐1/2 antibody test) in the EDs of a large academic medical center and an affiliated community hospital in Durham, North Carolina. Results In total, 5443 ED patients were offered HIV testing. The overall acceptance rate was 66.9% (3639/5443). Younger persons were significantly more likely to accept testing (78.2% for 18–29 years old vs 67.1% for ≥30 years old; P < 0.001) as were Black participants (72.6% Black vs 66.5% White; P < 0.001). Acceptance rates improved significantly after opt‐out oral consent replaced written consent (71.3% vs 63.1%; P < 0.001). Seven new HIV diagnoses were confirmed during the testing program, resulting in a seropositivity rate of 0.19% (7/3639). There were 8 false–positive rapid oral HIV tests (positive predictive value = 46.7%). Conclusions Although the number of new HIV diagnoses was low, implementation of this rapid, non‐targeted ED screening program was feasible with high acceptance rates, particularly after introducing the opt‐out oral consent approach.